The obsidian mirror - Maria do Socorro Reis Amorin (Ilha do Desterro)
The author James Norman is an American who has always lived in Mexico during the summer. He seems to love Mexican - Indian traditions and he is well acquainted with the pre-historic culture as it is shown in his book: "The Obsidian Mirror". "The Obsidian Mirror" is a mysterious story about an archeologist: Quigley that lives in a small village in Mexico-San Marcos. He is searching for antiques that belong to some tribes of pre-historic Indians in order to find out their mysteries. Quigley becomes so engaged in his work that his mind has reached a stage that is impossible to separate between Quigley the archeologist, and Quigley as an ancient Indian. The culture, the myth, the sensation of Omen - characteristics of the Indians are within himself. As a result, Quigley acts sometimes as a real Indian.